MICROSTRUCTURING IN PLATINUM AND STAINLESS STEEL MATERIAL USING PICOSECOND Nd:YAG LASER - Adijāns, Imants; Kažmere, Ieva; Horn, Alexander (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2019)
The number of products manufactured in micro- and nano-size is increasing every year. In electronics, medicine, biology and other industries, because of the rapid development of technologies, is possible to produce new or already used products in very small sizes, maintaining or even improving the efficiency of the product or giving an opportunity to use them for new purposes. Currently available pico- and femtosecond lasers ensure the production of such products in very small sizes. In this study, the treatment of platinum and stainless steel using a picosecond Nd:YAG laser with a wavelength of 1064nm, was considered. The obtained results for the laser ablation process of these materials will be useful for further research in the field of laser microprocessing.